Efficacy and Safety of Adding Immune Checkpoint Inhibitors to Neoadjuvant Chemotherapy Against Triple-Negative Breast Cancer: A Meta-Analysis of Randomized Controlled Trials - Li, Yunhai; Xing, Lei; Li, Fan; Liu, Hong; Gan, Lu; Yang, Dejuan; Wang, Mengxue; Yin, Xuedong; Li, Hongyuan; Ren, Guosheng (Frontiers in Oncology, 2021)
Background: Immune checkpoint inhibitors (ICIs) have shown promising anti-tumor activity in multiple malignances including breast cancer. However, the responses can vary. This meta-analysis was conducted to evaluate the efficacy and safety profile of adding ICIs to neoadjuvant chemotherapy against triple-negative breast cancer (TNBC) and assess correlation of PD-L1 tumor status with responses. Methods: Eligible studies were retrieved from the PubMed, Embase, and Web of Science databases. Randomized controlled trials (RCTs) that investigated ICI-containing versus ICI-free neoadjuvant therapy were included in this study. Meta-analyses were performed using Review Manager Version 5.2 software. Results: This study included four RCTs containing 1795 patients with early TNBC. Compared with ICI-free neoadjuvant therapy, ICI-containing neoadjuvant therapy significantly increased the pathological complete response (pCR) rates in TNBC (odds ratio [OR] = 2.14, 95% confidence interval [CI]: 1.37–3.35, P < 0.001). In subgroup analysis, the addition of ICI to neoadjuvant chemotherapy was significantly associated with increased pCR rate in both PD-L1-positive TNBC (OR = 1.79, 95% CI: 1.33–2.41, P < 0.001) and PD-L1-negative TNBC (OR = 1.84, 95% CI: 1.14–2.99, P = 0.01). Patients with TNBC receiving ICI-containing neoadjuvant therapy had a better event-free survival (hazard ratio = 0.66, 95% CI: 0.48–0.89, P = 0.007) than those who receiving ICI-free neoadjuvant therapy. A significantly higher risk of adverse events including adrenal insufficiency, increased aspartate aminotransferase, dry skin, hepatitis, hyperthyroidism, hypothyroidism, infusion related reaction, pyrexia, and stomatitis was associated with ICI-containing neoadjuvant therapy.